Investigations on microstructure and mechanical properties of Mg-5wt.% Cu-TiB2 composites produced via powder metallurgy route - Stalin B.; Ravichandran M.; Mohanavel V.; Raj L.P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Magnesium alloy matrix composite reinforced with constant weight fraction of 5% Cu and various weight fractions of (0%, 5%, 10%, 15%) titanium diboride (TiB2) fabricated by Powder Metallurgy route. In this work, the mechanical properties like hardness, impact strength, compression strength, and wear rate of the Mg-Cu alloy and fabricated composites were investigated. The results showed that the addition of weight percentage of 15% TiB2 increased the hardness value about 58.56 HV, due to better bonding between the Mg-Cu and TiB2. Further, impact and compressive strengths improved, as the weight percentage of TiB2 increased. Uniform distribution of reinforced particles enhanced the impact strength and the work hardening effect improved the compression strength. Moreover, the wear rate decreased about 0.0112 mg by the addition of weight percentage of 15% TiB2. X-ray diffraction (XRD) analysis was carried out for each composition. Optical microscopy, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) tests were conducted to study the characterization of the base alloy and the prepared new composite.